2023
DOI: 10.3389/fneur.2023.1158977
|View full text |Cite
|
Sign up to set email alerts
|

Should we offer deep brain stimulation to Parkinson’s disease patients with GBA mutations?

Abstract: Parkinson’s disease (PD) patients who are carriers of glucosylceramidase β1 (GBA1) gene mutations typically have an earlier age at onset and a more aggressive disease course, with a higher burden of neuropsychological issues. The use of deep brain stimulation (DBS) in PD patients with disabling motor fluctuations and absence of dementia is a widespread therapeutic option, often with good results in terms of improvement in activities of daily living and quality of life. Although all PD patients, when fulfilling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Our data are also insufficient to perform an adequate stratification of patients’ outcomes in relation to their genetic status. Genetic characterization of patients enrolled for DBS will become very important in the future, especially in the light of recent evidence on prognostic implications for patients with genetically determined PD undergoing STN-DBS, like GBA-mutated patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are also insufficient to perform an adequate stratification of patients’ outcomes in relation to their genetic status. Genetic characterization of patients enrolled for DBS will become very important in the future, especially in the light of recent evidence on prognostic implications for patients with genetically determined PD undergoing STN-DBS, like GBA-mutated patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Parkinson's disease patients who carry a single GBA variant present with earlier onset of symptoms and a more aggressive disease course. Certain variants of the GBA gene carry a higher risk in this context (101). While STN-DBS has been associated with good motor outcomes in this population, it has been suggested that it may have negative effects on cognitive outcomes.…”
Section: Other Neurometabolic Conditionsmentioning
confidence: 98%
“…Our study demonstrated that GBA carriers undergoing STN‐DBS had good motor and pharmacological outcomes, but they experienced the worst cognitive outcome and the worst quality of life. To date, the most rational approach would be to detect the presence of GBA variants through sequencing techniques in candidates for DBS and to discuss thoroughly with the patient and the caregiver the potential risks 81 . A personalized approach aided by genetic information and variant‐based risk stratification should be implemented, whenever possible.…”
Section: Individual Patient Datamentioning
confidence: 99%